Is there any favourite-longshot bias in the Hong Kong racetrack betting market? - YIP, Ka Shing (2007)
The favourite longshot bias has become the central tendency of betting market research. Many researchers find out that bettors tends to under-bet the favourite and over-bet the longshot. In our research, we examine the relationship between odds and the winning probabilities in order to test for the existence of a favourite longshot bias in Hong Kong using data in the 2006-2007 seasons. We show that the FL bias does not exist in the Hong Kong horse racing betting market. Also, we find no evidence of the risk preference and the insider trader effect in Hong Kong. We suggest that prospect theory may be a useful framework which to conduct future research in this topic.